2014
DOI: 10.1038/labinvest.2014.57
|View full text |Cite
|
Sign up to set email alerts
|

Role of local bioactivation of vitamin D by CYP27A1 and CYP2R1 in the control of cell growth in normal endometrium and endometrial carcinoma

Abstract: Vitamin D (VD) deficiency has been suggested as a risk factor for cancer. One recognized mechanism is that the low-serum 25-hydroxyvitamin D (25(OH)D) of VD deficiency reduces intratumoral 25(OH)D conversion to 1a,25-dihydroxyvitamin D (1,25D, the hormonal form of VD), compromising 1,25D-VD receptor (VDR) antitumoral actions. Reduced tumoral VDR and increased CYP24A1, the enzyme that degrades 1,25D and 25(OH)D, further worsen cancer progression. Importantly, in cells expressing CYP27A1 and/or CYP2R1, which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 50 publications
2
33
0
3
Order By: Relevance
“…In this case, tissue samples in different phases of the endometrial cycle were obtained from 60 women (age ranged from 25 to 55, mean = 43, 20 samples in proliferative and 40 samples in secretory phase), samples were embedded in paraffin blocks and tissue microarrays were analyzed. A decrease in the total expression of VDR in the proliferative endometrium compared with the secretory phase (fold change 3.17, p = 0.00002) as well as an increase in the cytosolic VDR protein expression (fold change 1.81, p = 0.006) [30] were observed.…”
Section: Vitamin D and Normal Endometriummentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, tissue samples in different phases of the endometrial cycle were obtained from 60 women (age ranged from 25 to 55, mean = 43, 20 samples in proliferative and 40 samples in secretory phase), samples were embedded in paraffin blocks and tissue microarrays were analyzed. A decrease in the total expression of VDR in the proliferative endometrium compared with the secretory phase (fold change 3.17, p = 0.00002) as well as an increase in the cytosolic VDR protein expression (fold change 1.81, p = 0.006) [30] were observed.…”
Section: Vitamin D and Normal Endometriummentioning
confidence: 99%
“…Some studies used the cells isolated from tissue that could be contaminated with immune cells present in the endometrium [30] while others used immunohistochemistry analysis of embedded tissue [31]. The selection of the control patients may be as well a source of variability in the different studies.…”
Section: Vitamin D and Normal Endometriummentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that CYP2R1 (and CYP27B1) expression was increased in endometrial cancer, as an autocrine/paracrine defense mechanism (Bergada et al, 2014). Similarly, CYP2R1 expression was higher in oral squamous cell carcinomas (OSCCs), compared with the adjacent normal mucosa.…”
Section: Vitamin D 3 25 Hydroxylases (Cyp2r1 Cyp27a1) In Cancermentioning
confidence: 99%